2016
DOI: 10.1039/c6ra15584g
|View full text |Cite
|
Sign up to set email alerts
|

The seed stimulant effect of nano iron pyrite is compromised by nano cerium oxide: regulation by the trace ionic species generated in the aqueous suspension of iron pyrite

Abstract: A brief seed pretreatment of 12 hours, in an aqueous suspension of synthesized nano iron pyrite (FeS2), significantly increases the yield of spinach and other crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…Pyrite has wide area of applications (Figure ) such as energy storage and conversion field: photovoltaics,, photocatalytic hydrogen production, batteries, supercapacitors, photocapacitors, thermoelectricity;, electronics,, optoelectronics, spintronics; environmental applications; hydrogenation; sensors; agriculture, and emerging biomedical field …”
Section: Introductionmentioning
confidence: 99%
“…Pyrite has wide area of applications (Figure ) such as energy storage and conversion field: photovoltaics,, photocatalytic hydrogen production, batteries, supercapacitors, photocapacitors, thermoelectricity;, electronics,, optoelectronics, spintronics; environmental applications; hydrogenation; sensors; agriculture, and emerging biomedical field …”
Section: Introductionmentioning
confidence: 99%
“…In their study, they found the increasing dose‐dependent effect of Fe 2 O 3 NPs on the spinach plants. Likewise, Das et al [30] investigated the seed stimulant effect of nano iron pyrite (FeS 2 ) and nano cerium oxide (CeO 2 ) in the regulation of trace ionic species generated in the aqueous suspension of iron pyrite. They also found that it delays germination of seeds, whereas FeS 2 hastens germination.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported not only phytotoxicity and accumulation of NPs but also growth promoting effects [22, 24, 25, 27, 31]. Considering the toxicity issue, an alternative to synthetic fertilisers in agricultural system is necessary to maintain ecosystems and to develop sustainable agriculture [30].…”
Section: Introductionmentioning
confidence: 99%
“…Spinach treated with nano iron pyrite (FeS2) increased the germination whereas and CeO2 delayed the germination [19]. MWCNTs improved germination by 90% in two days as against 71% in untreated samples [20]. Rice seeds treated with nano-CuO reduced the germination [21].…”
Section: Nanoparticles For Seed Germination Plant Growth Yield and Qu...mentioning
confidence: 99%